ANALISIS KINERJA KEUANGAN LEMBAGA PERKREDITAN DESA ADAT BANGKANG BAKTISERAGA MENGGUNAKAN ANALISIS DU PONT - Putri Anggreni (Universitas Bunda Mulia, 2019)
The management is required to always introspect condition of the company, especially in terms of financialnya, because it holds the key to life and death of the company. The condition that the company should always be monitored, can be done by analyzing the financial statements themselves, which generally consist of a balance sheet and income statement. Through the analysis of the financial statements can be found successful achievement of achievement demonstrated by the absence of a healthy financial statements, which is the basis of performance appraisal or part of the existing work in the company.Used in this study to analyze the financial statements is Du Pont, aims to determine the state of Indigenous Village Credit Institutions Bangkang Baktiseraga which was done by measuring the financial performance. Analysis of Du Pont is one of the techniques that are thorough financial analysis, management can determine the level of efficiency of capital use. Financial performance results obtained from the calculation of Return on Assets and Return on Equity from year to year decline, but is still in good health as above average standard of Bank Indonesia. Village Credit Institutions should determine the condition of future performance in order to be a better performance than the previous year and the profit achieved will also be maximized. Key words: Financial Performance, LPD, ROA, ROE, Du Pont Analysis